Ambiguous and Deeply Differentiated: Kierkegaard’s Relations to Hegel - Grøn, Arne (KIERKEGAARDIANA, 2004)
A Critique of Jon Stewart’s Kierkegaard’s Relations to Hegel Reconsidered Cambridge: Cambridge University Press, 2003; xviii + 695 pp.